Abnormal Left-Sided Orbitomedial Prefrontal Cortical–Amygdala Connectivity during Happy and Fear Face Processing: A Potential Neural Mechanism of Female MDD - Almeida, Jorge; Kronhaus, Dina; Sibille, Etienne; Langenecker, Scott; Versace, Amelia; LaBarbara, Edmund; Phillips, Mary L. (Frontiers in Psychiatry, 2011)
Background: Pathophysiologic processes supporting abnormal emotion regulation in major depressive disorder (MDD) are poorly understood. We previously found abnormal inverse left-sided ventromedial prefrontal cortical- amygdala effective connectivity to happy faces in females with MDD. We aimed to replicate and expand this previous finding in an independent participant sample, using a more inclusive neural model, and a novel emotion-processing paradigm. Methods: Nineteen individuals with MDD in depressed episode (12 females), and nineteen healthy individuals, age and gender matched, performed an implicit emotion processing and automatic attentional control paradigm to examine abnormalities in prefrontal cortical-amygdala neural circuitry during happy, angry, fearful and sad face processing measured with functional magnetic resonance imaging in a 3Tesla scanner. Effective connectivity was estimated with Dynamic Causal Modelling in a trinodal neural model including two anatomically defined prefrontal cortical regions, ventromedial prefrontal cortex and subgenual cingulate cortex(sgACC), and the amygdala. Results: We replicated our previous finding of abnormal inverse left-sided inverse top-down ventromedial prefrontal cortical-amygdala connectivity to happy faces in females with MDD (p=.04), and also showed a similar pattern of abnormal inverse left-sided sgACC-amygdala connectivity to these stimuli (p=0.03). These findings were paralleled by abnormally reduced positive left-sided ventromedial prefrontal cortical-sgACC connectivity to happy faces in females with MDD (p=0.008), and abnormally increased positive left-sided sgACC-amygdala connectivity to fearful faces in females, and all individuals, with MDD (p=0.008;p=0.003). Conclusions: Different patterns of abnormal prefrontal cortical-amygdala connectivity to happy and fearful stimuli might represent neural mechanisms for the excessive self-reproach and comorbid anxiety that characterize female MDD.